Exploring the Influencing Paths of Villagers’ Participation in the Creation of Micro-Landscapes: An Integrative Model of Theory of Planned Behavior and Norm Activation Theory - Cheng, Huishan; Rui, Quanquan; Yu, Kunyong; Li, Xiaohe; Liu, Jian (Frontiers in Psychology, 2022)
Villager participation has become a key breakthrough in rural landscape governance. Using the theory of planned behavior and the norm activation theory as frameworks, this study adopts the structural equation model to explore the influencing mechanism of villager participation in rural micro-landscapes based on data gathered from 414 villagers in a rural micro-landscape construction survey in Jinjiang, China. The results indicate that (1) integrated planned behavior theory and norm activation theory can better explain the influencing mechanism of villagers’ participation in rural micro-landscape construction; (2) perception, norm, attitude, and control dimensions significantly influence villagers’ participation behavior intention. The attitude dimension had the greatest influence, followed by the normative and control dimensions, while the perception dimension had the least influence on the procedure; and (3) according to the mediation results, natural environment perception, social environment perception, personal norm, social norm, participation attitude, result awareness, and self-efficacy all exert indirect effects on participation behavior based on villagers’ participation behavioral intention. The largest median effect value was result awareness, followed by personal norm, participation attitude, natural environment awareness, self-efficacy, and social norm. This study expands the theoretical framework and research content of planned behavior and clarifies the mechanism of the influencing factors of villagers’ participation in rural micro-landscapes, extending the theory of planned behavior to the research field of villagers’ participation, which has a guiding role in promoting the co-construction, co-governance, and sharing of rural landscapes.